If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 + 6y = 7y + 2y Combine like terms: 7y + 2y = 9y -36 + 6y = 9y Solving -36 + 6y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -36 + 6y + -9y = 9y + -9y Combine like terms: 6y + -9y = -3y -36 + -3y = 9y + -9y Combine like terms: 9y + -9y = 0 -36 + -3y = 0 Add '36' to each side of the equation. -36 + 36 + -3y = 0 + 36 Combine like terms: -36 + 36 = 0 0 + -3y = 0 + 36 -3y = 0 + 36 Combine like terms: 0 + 36 = 36 -3y = 36 Divide each side by '-3'. y = -12 Simplifying y = -12
| 3m-2=9 | | -2(6x+8)+7x=3x-2(12+4x) | | -5=-0.5g-2 | | 8(5x-14)=208 | | 9.47x=7.4x-8.81 | | 2n^2-2=0 | | 3x-7=5x+4 | | 2+-1.5+0.5= | | 4(7x+8)=6(8x-11)-2 | | -69=-7-p | | Y=-5x+12 | | 42+3x=180 | | -3n-1=-37 | | -3n-=-37 | | 12-(-x)+8=18 | | 2a-5=-38 | | -4=-3t+2 | | 4y=5x+12 | | Y=5x+12 | | 15k-4=21 | | (4w+1)(6+w)=0 | | 8a-12=6 | | (3x^2)-8x=0 | | 4x-3(2x-3)=11 | | 0.7(3x-5)+3.9=14.5 | | -9=3+6k | | 3b-2(b+4)=8(b-1) | | x-4+6x-8x=3 | | 3(4X-3)=-81 | | 8(2x+3)-5=16x+19 | | -7(3v+6)=-7v+32 | | 3(x-7)=23-(3x+2) |